Perbedaan Pengetahuan Dan Sikap Sebelum Dan Sesudah Intervensi Menggunakan Media Video Tentang Bahaya Pernikahan Dini Pada Siswa Siswi SMP Di Kota Cirebon Tahun 2022 - Yuhandini, Diyah Sri; Jubaedah, Entin; Sriyatin, Sriyatin (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Early marriage is known as a global problem experienced in many countries. Based on Cirebon city marriage registration data for each sub-district, the number of marriages under 21 years old in 2020 is high (19.6%). Early marriage may affect the health condition of both the mother and the baby. Health promotion media is suitable to transfer any health information to adolescent groups. This study aimed to determine the effect of reproductive health education using video media on junior high school students' knowledge and attitudes about the dangers of early marriage in Cirebon City in 2022. The quasi-experimental design with one group pre-test and post-test methods was used. The sample was recruited using purposive sampling to the 102 people population of students in five schools around Cirebon City. Data were analyzed using univariate and bivariate analysis by the Mc-Nemar test. An increase in knowledge in the good category was obtained from 57.8% to 77.5% also in supportive attitude from 54.9% to 75.5% after the intervention. The results showed significant differences in knowledge (p-value = 0.001) and attitudes (p-value = 0.001) before and after the video media intervention. It is highly recommended to enter any material related to early marriage into the junior high school curriculum also extracurricular activities at school.